The political economy of government auditing : financial governance and the rule of law in Latin America and beyond - Santiso, Carlos (Abingdon [England] ; New York : Routledge-Cavendish, 2009)
This book is an important contribution to our understanding of how curruption can be prevented by strenghtening those institutions tasked with srutinizing government and overseeing public finances.
Budget institutions and financial governance -- Political economy of budget oversight and external auditing -- Institutional arrangements for external auditing -- The board model and the case of Argentina -- The court model and the case of Brazil -- The monocratic model and the case of Chile -- Government auditing in transition -- Conclusions : auditing, accountability and anticorruption.
A GlassHouse book.
Includes bibliographical references (p. [154]-168) and index.
aia 10/05/13
Loan
Keywords: Finance, Public -- Latin America -- Accounting; Finance, Public -- Accounting -- Law and legislation -- Latin America